Menakar Peran Relawan Politik Pasca Kontestasi Presidensial 2014 - Bambang Arianto (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2016)
This article explains that the role of post-conflict political volunteers in 2004, who began with the presidential activity mapping and projection of the volunteers. It was to find out the tactical steps taken by the political volunteers, especially in issues of politics and government. This study revealed that volunteers more engaged in social media, then divides typology into a community volunteer and non-volunteer community. Form the two typology of volunteers turned out more volunters who choose passivity rather than active. Passive attituded intended to be a controller of goverment, while the more active attituded as the guardian of power. This article argues that the role of volunteers in post-conflict digital style presidential politics in 2014 more strengthen the institutionalization of digital activism for political aducation of the public.